Prediabetes Risk Evaluation Scoring System [PRESS]: A simplified scoring system for detecting undiagnosed Prediabetes. Issue 1 (February 2019) - Rajput, Rajesh; Garg, Keshav; Rajput, Meena
Highlights: Prevalence of diabetes and pre-diabetes are increasing globally. We report a Scoring System [PRESS] for identifying pre-diabetic subjects. Out of 892 subjects studied, 160 were found to be pre-diabetic (17.93%). Score of >45 has best predictive value. PRESS is a simple & noninvasive screening tool to identify undiagnosed prediabetes Abstract: Objective: To develop a simplified scoring system for detecting undiagnosed prediabetes among healthy adult population of Haryana, India. Material & Methods: This cross-sectional study was a household survey which involved 892 healthy adults >18 year of age who were subjected to an oral glucose tolerance test. Sensitivity, specificity, positive and negative predictive value and area under the receiver operating characteristic (ROC) curve and the optimal cut off points for identifying undiagnosed prediabetes were calculated. Results: Out of 892 subjects studied, 459 were males and 433 were females and 160 were found to be prediabetic (17.93%). At an optimal score of >45 the area under the ROC curve is 0.785 with sensitivity, specificity, positive and negative predictive value of 84.37%, 58.47%, 30.75 and 94.48% respectively. Conclusions: Prediabetes Risk Evaluation Scoring System (PRESS) a simple and non-invasive screening tool to identify adult individuals having undiagnosed prediabetes.